ANALISIS PERBANDINGAN KUAT TEKAN BETON NORMAL DENGAN BETON CAMPURAN BAN BEKAS - Muh. Ilham Nurrosyid; Hanggara Yudi Susanto; Hartopo Hartopo; Totok Apriyanto (Jurnal Teknik Indonesia, 2024)
This study evaluates the comparison of compressive strength between conventional concrete and concrete mix with used tire aggregate, focusing on its influence on compressive strength and concrete weight. The testing used cylindrical specimens with variations of used tire addition at 3%, 6%, 9%, and 12% of the coarse aggregate volume. The targeted concrete design strength is fc' 20 MPa at 28 days. Experimental methods were employed to compare their mechanical properties, measuring compressive strength and concrete weight across different mix compositions. The results for normal concrete yielded an average of 30.96 MPa, while for 3% tire mix yielded an average of 30.12 MPa, 6% tire mix yielded an average of 25.51 MPa, 9% tire mix yielded an average of 22.51 MPa, and 12% tire mix yielded an average of 21.54 MPa. The reduction in concrete weight for 3% tire mix was 0.035 kg from normal concrete, for 6% tire mix was 0.04 kg from normal concrete, for 9% tire mix was 0.23 kg from normal concrete, and for 12% tire mix was 0.35 kg from normal concrete. The study findings indicate that concrete mix with used tire aggregate exhibits competitive compressive strength with conventional concrete, while showing a tendency towards lower weight. The implication is that concrete mix with used tire aggregate has the potential to be a lighter and mechanically strong alternative. This study provides important insights for the construction industry in seeking more sustainable and cost-efficient solutions, while reducing the environmental impact of used tire waste.